Three-antibody classifier for muscle invasive urothelial carcinoma and its correlation with p53 expression. Issue 11 (8th June 2021) - Olkhov-Mitsel, Ekaterina; Hodgson, Anjelica; Liu, Stanley K; Vesprini, Danny; Xu, Bin; Downes, Michelle R
Abstract : Aims: To assess the utility of a three-antibody immunohistochemistry panel to classify muscle invasive bladder cancers (MIBCs) in correlation with morphological features and p53 status. Methods: A retrospective review of 243 chemotherapy naïve MIBC cystectomy specimens was performed to assess morphological features. A tissue microarray was sequentially stained with CK5/6, GATA-3 and p16. Subgroups were assigned as basal-like (CK5/6+, GATA3−) and luminal (CK5/6−, GATA3+), with the latter subdivided into genomically unstable (GU, p16+) and urothelial like (Uro, p16−) subgroups. p53 staining was assessed as abnormal/wild type. Cases from the The Cancer Genome Atlas (TCGA) portal were assessed as external validation. Results: We identified 78.8% luminal, 21.2% basal cases within our cohort and 63.4% luminal, 36.6% basal in the TCGA dataset. Divergent differentiation (p<0.001) was significantly associated with basal-subtype cases in both cohorts. Within the luminal subgroup (n=186), 81 cases were classified as GU and 105 as Uro. Abnormal p53 staining was noted in 48.0% of basal, 80.2% GU and 38.1% Uro cases. Further, basal-subtype tumours significantly correlated with disease-specific death compared with Uro cases in multivariate survival analysis. Conclusions: This retrospective study demonstrates the potential utility of a three-antibody immunohistochemistry panel to differentiate luminal and basal MIBC.